Relações intersemióticas em artigos audiovisuais de protocolo de pesquisa de biologia - Milani, Victor Gomes (2017)
In this master thesis text, we present the research entitled Intersemiotic Relations in Biology Research Protocol Audiovisual Articles, started in 2016, under the supervision of Professor. Graciela Rabuske Hendges and linked to the umbrella project Critical Analysis of Multimodality: language science for multiliteracies (HENDGES, 2017). The point of departure was the definition of the object of analysis: the Research Protocol Audiovisual Articles (RPAA), published in the Journal of Visualized Experiments (JoVE) in order to continue and deepen the previous study on the same genre carried out during undergraduation (MILANI, 2014). Six Biology Audiovisual Research Articles (ARAs) to compose the corpus were selected. Concerning theory and methodology, this research intends to carry out Critical Genre Analysis (CGA) (MOTTA-ROTH, 2008; MOTTA-ROTH; HEBERLE; 2015) along with Multimodal Discourse Analysis (MDA) (O’HALLORAN, 2004) because the analysis took into account verbal and visual semiotic modes, focusing on the way such modes engineer their semiotic relation and how they function in the rhetorical organization of this genre. This research also considered previous studies by Silva (2015a) and Souza (2015a) on the interpersonal and ideational dimensions of the RPAAs, respectively. We defined the Verbal-Visual Mise-èn-Scene (VVMS) as minimal units to be analyzed in the ARAs. Results on intersemiotic relations analysis of the corpus showed that intersemiotic relations are constructed differently within the three meaning dimensions proposed by Systemic-Functional Linguistics (SFL) and are similar to logic-semantic relations principles (HALLIDAY; HASAN, 1989; HALLIDAY, 1985; 1994; HALLIDAY; MATTHIESSEN, 2004). Their patterns corroborate and amplify the rhetorical organization of the ARAs mapped in previous studies (SILVA, 2015a; SOUZA, 2015a).